(untitled) (American International Journal of Sciences and Engineering Research, 2021)
The current research compared and analysed the tensile strength of silver soldered stainless steel and cobalt-chromium orthodontic wire joints with band material The effect of joint site planning on various orthodontic joining configurations was investigated. A total of sixty wire specimens were chosen, thirty in the stainless-steel group and thirty in the cobalt – chromium group. Again, each group’s sample was divided into three subgroups, namely End – End, Round, and Orthodontic band material. The study findings suggested all three configurations can be used to make silver soldered joints regardless of the wire consistency. When subjecting the wire to joint site planning, however, stainless steel wire should be used with its limitations in mind.